Chloroquine induces eryptosis in P. falciparum-infected red blood cells and the release of extracellular vesicles with a unique protein profile - Carrera-Bravo, Claudia; Zhou, Tianchi; Chu, Trang; Hang, Jing Wen; Modh, Harshvardhan; Huang, Chenyuan; Zhang, Sitong; Hao, Haining; Cabada-García, María José; Malleret, Benoit; Wacker, Matthias G.; Wang, Jiong-Wei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMalaria is a vector-borne parasitic disease that affects millions worldwide. To achieve the objective set by the World Health Organization of reducing malaria cases by 2030, antimalarial drugs with novel modes of action are required. Previously, a novel mechanism of action of chloroquine (CQ) was reported involving features of programmed cell death in the parasite, mainly characterized by calcium efflux from digestive vacuole permeabilization. Increased intracellular calcium induces suicidal death of erythrocytes, a process known as eryptosis. This study aimed to identify the hallmarks of eryptosis due to calcium redistribution and examine the downstream cellular effects during CQ treatment in infected red blood cells (iRBCs).MethodsSynchronized Plasmodium falciparum 3D7 cultures at mid-late trophozoites were treated with CQ and other antimalarial compounds for 10 hours. Eryptotic markers, including phosphatidylserine (PS) exposure, cell shrinkage and membrane blebbing, were assessed by flow cytometry, scanning electron microscopy and western blot, respectively. Extracellular vesicles (EVs) were isolated from 3D7 malaria culture supernatants using differential ultracentrifugation, followed by their physical and proteomic characterization. THP-1-derived macrophages were stimulated with EVs to determine parasite-host interactions, as indicated by cytokine levels and transcriptomic analysis.ResultsIncreased PS exposure, cell shrinkage, and membrane blebbing were observed, delineating an eryptotic phenotype in the host RBCs. Notably, the outward budding and blebbing of the iRBC plasma membrane led to the formation of EVs, which are complex structures with unique functional properties. Proteomic characterization of EVs from CQ-treated iRBCs revealed a high enrichment of proteasome and ribosome protein clusters. This unique EV cargo did not influence the parasite growth rate but might activate IFN signaling pathways mediated by IL-6 in THP-1-derived macrophages.ConclusionThese findings provide new insights into a novel drug-induced cell death mechanism that targets the parasite and specific components of the infected host RBC.